Metode Pemeriksaan pada Sistem TNM untuk Karsinoma Sel Skuamosa Kulit - Alida Widiawaty; Rahadi Rihatmadja; Aviyanti Djurzan (Jurnal Ilmu Kedokteran, 2016)
Squamous cell carcinoma is a nonmelanoma skin malignancy derived from suprabasal keratinocytes. Although completeremission can occur after surgery, patients with advanced stage have poor prognosis. Some cases of high risk canmetastasis. Lymph node’s metastasis occur in approximately 4% of cases with 1,5% mortality rate. Difficulties inidentifying high risk cases and the absence of management guideline are contributing factors in patient mortality.Staging is a process to determine the presence and progression of cancer.